Genome Modification Leads to Phenotype Reversal in Human Myotonic Dystrophy Type 1 Induced Pluripotent Stem Cell‐Derived Neural Stem Cells. (June 2015) - Xia, Guangbin; Gao, Yuanzheng; Jin, Shouguang; Subramony, S.H.; Terada, Naohiro; Ranum, Laura P.W.; Swanson, Maurice S.; Ashizawa, Tetsuo
Abstract Myotonic dystrophy type 1 (DM1) is caused by expanded CTG repeats in the 3'‐untranslated region (3′ UTR) of the DMPK gene. Correcting the mutation in DM1 stem cells would be an important step toward autologous stem cell therapy. The objective of this study is to demonstrate in vitro genome editing to prevent production of toxic mutant transcripts and reverse phenotypes in DM1 stem cells. Genome editing was performed in DM1 neural stem cells (NSCs) derived from human DM1 induced pluripotent stem (iPS) cells. An editing cassette containing SV40/bGH polyA signals was integrated upstream of the CTG repeats by TALEN‐mediated homologous recombination (HR). The expression of mutant CUG repeats transcript was monitored by nuclear RNA foci, the molecular hallmarks of DM1, using RNA fluorescence in situ hybridization. Alternative splicing of microtubule‐associated protein tau (MAPT) and muscleblind‐like (MBNL) proteins were analyzed to further monitor the phenotype reversal after genome modification. The cassette was successfully inserted into DMPK intron 9 and this genomic modification led to complete disappearance of nuclear RNA foci. MAPT and MBNL 1, 2 aberrant splicing in DM1 NSCs were reversed to normal pattern in genome‐modified NSCs. Genome modification by integration of exogenous polyA signals upstream of the DMPK CTG repeat expansion prevents the production of toxic RNA and leads to phenotype reversal in human DM1 iPS‐cells derived stem cells. Our data provide proof‐of‐principle evidence that genome modification may be used to generate genetically modified progenitor cells as a first step toward autologous cell transfer therapy for DM1. Stem Cells2015;33:1829–1838